Susan I. Rotroff. The Athenian Agora XXXIII: Hellenistic Pottery, the Plain Wares. pp. 480, with 98 ills and 90 plates. 2006. Princeton NJ: American School of Classical Studies at Athens. ISBN 978-0-87661-233-0, hardback $150. - van der Enden, Mark (Journal of Greek Archaeology, 2020)
Rotroff’s Hellenistic Pottery, the Plain Wares is one of the key Hellenistic Pottery publications available to specialists in the field. The publication, by now more than a decade old, is still a shining example of the ideal pottery publication. It combines a rigorous, exhaustive and authoritative presentation and discussion of ceramic data with substantial contextual analysis. The lavishly illustrated volume joins its sister volumes, Agora XXIX and XXII, in providing a complete picture of the Hellenistic period pottery attested at the Athenian Agora.